Basic Frameworks for Decisions - Wilson, Charles Z.; Alexis, Marcus (Academy of Management Journal, 1962)
Presents a panoramic view of frameworks and related concepts underlying the wide range of decision models. Literature and researches made on decision-making; Elements of decision-making; Nature of closed and open decision models; Behavioral foundations of close and open decision models.